2016
DOI: 10.1088/0953-4075/49/5/055203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular frame photoelectron angular distributions for core ionization of ethane, carbon tetrafluoride and 1,1-difluoroethylene

Abstract: Molecular frame photoelectron angular distributions (MFPADs) are measured in electron-ion momentum imaging experiments and compared with complex Kohn variational calculations for carbon K-shell ionization of carbon tetrafluoride (CF 4 ), ethane (C 2 H 6 ) and 1,1-difluoroethylene (C 2 H 2 F 2 ). While in ethane the polarization averaged MFPADs show a tendency at low energies for the photoelectron to be emitted in the directions of the bonds, the opposite effect is seen in CF4. A combination of these behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…One would assume that the former must be rather small since Auger decay is mostly an intershell process. The latter on the other hand is thought of as having a big influence in core-hole localization [41] but also may be rather subtle for homonuclear molecules; however, it has just been shown in photofragmentation of C 2 H 2 that the isomerization process starts very early in the Auger decay; in fact it begins right within the Franck-Condon region of the transition [42]. Moreover, given the high Auger electron kinetic energy, and thus a wavelength in the order of the distance between the atomic constituents, multiple scattering and interference effects of the Auger electrons are expected to be sensitive to the molecular structure [43,44], which dissociates into two or more fragments.…”
Section: Introductionmentioning
confidence: 99%
“…One would assume that the former must be rather small since Auger decay is mostly an intershell process. The latter on the other hand is thought of as having a big influence in core-hole localization [41] but also may be rather subtle for homonuclear molecules; however, it has just been shown in photofragmentation of C 2 H 2 that the isomerization process starts very early in the Auger decay; in fact it begins right within the Franck-Condon region of the transition [42]. Moreover, given the high Auger electron kinetic energy, and thus a wavelength in the order of the distance between the atomic constituents, multiple scattering and interference effects of the Auger electrons are expected to be sensitive to the molecular structure [43,44], which dissociates into two or more fragments.…”
Section: Introductionmentioning
confidence: 99%
“…4 we show the results of experiments and theory at 3 and 12 eV for the case of the polarization perpendicular to the recoil axis, for which the RFPADs are not cylindrically symmetric, even though they represent averages around the dissociating C-F bond. Here, the photoelectron primarily exhibits the angular effect of being ejected by the incident radiation along the polarization axis, as is frequently seen in MFPADs [15,19], and the effects of localization on the RFPAD are much less pronounced. Indeed, the calculated RFPADs for localized and delocalized F core vacancies in this case are too close in shape to be distinguished by experiment.…”
mentioning
confidence: 86%
“…In each experiment the photoelectron was recorded in coincidence with a CF 3 + and F + ion on a shot-by-shot basis and for known orientations of the linear polarized light. Other details of the experimental setup were the same as those in an earlier COLTRIMS study of carbon K-shell ionization in CF 4 [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In that context it has been observed that, while a coupled channels treatment is frequently necessary for valence photoionization of molecules, the single-channel static-exchange approximation can provide accurate results for core ionization or inner-shell ionization when the ionized state is not degenerate or nearly degenerate. Using this simpler approximation, which ignores correlation between the continuum and bound electrons, combined experimental and theoretical studies have uncovered "imaging" and "antiimaging" angular distributions in core and inner-shell ionization [6][7][8][9] and explored the consequences of corehole localization in molecules with symmetry equivalent atoms [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%